Implementation of Cooperative Learning Models of Think Pair Share (TPS) Type to Increase Participation Student on Mathematics Learning Outcomes - Nugroho, Sapto Sri; Suharto, Abdul Wachid Bambang (Jurnal Pendidikan Matematika IKIP Veteran Semarang, 2024)
Mathematics is a subject that has an important role in education. Mathematics is needed in every aspect of human life. Therefore every study program chosen by students cannot be separated from mathematics lessons. The purpose of this study are: (1) to increase participation mathematics teaching through a cooperative learning model and (2) to improve learning outcomes in mathematics education through collaborative learning models of Think Pairs Share in Class VII G students at SMPN 1 Purwokerto academic year 2022/2023.The method used in this study is a qualitative method with a case study approach. The subjects of this study were 34 students, 18 Male and 16 female students at SMPN 1 Purwokerto. Based on research, learning mathematics is through the form of collaborative learning Think Pairs Share, student participation in Algebra by 52,9% or 18 students in the pre-cycle (first stage), 66,2% or 23 students in cycle I and 79,4% or 27 students in cycle II (performance indicator 75%). Then, the student learning increased from 44,1% or 15 students in the previous cycle to 67,6% or 23 students in the end of cycle I and 82,4% or 28 students after completing the final exam of the cycle II (performance indicator 80%). In this study, the indicators of mathematics representation ability are visual representation, representation of mathematics equations and also representation of written text.